OQÍWSHÍLARDÍŃ ÓZBETINSHE KITAP OQÍW MÁDENIYATÍN QÁLIPLESTIRIW USÍLLARÍ - Pazılov, A.K.; Ilyasova, Z.U. (SCIENCE and SOCIETY, 2020)
The article deals with methods of forming the culture of independent reading of students.